DINAMIKA PSIKOLOGIS KEKERASAN SEKSUAL: SEBUAH STUDI FENOMENOLOGI - Fu'ady, Muh Anwar (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2011)
Purpose of this study was to find out how the sexual violence occurs, the psychological impact of sexual violence, and knowing how psychological dynamics of sexual assault victims. Subjects in this study were the two people taken purposively with the criteria had experienced sexual violence. Methodology in qualitative research is phenomenological. There are four processes in a phenomenological approach that is epoche, phenomenological reduction, imaginative variation and synthesis of meaning. Data analysis process involves bracketing, horizonalizing, and meaning units to get the textural description. The results of this study indicate that the psychological impact of the subjects who are victims of sexual violence is the presence of post-traumatic stress disorder. Besides having a psychological impact, psychological dynamics of the subjects in this study also have similarities, but there are some striking differences. The big difference in the impact and psychological dynamics is caused by several factors such as personality characteristics, how to solve problems, how to manipulate cognition, and social support.Â